Review on antibacterial biocomposites of structural laminated veneer lumber - Chen, Zi-Xiang; Lei, Qiong; He, Rui-Lin; Zhang, Zhing-feng; Khan Chowdhury, Ahmed Jalal (Elsevier, 2016)
In this review, the characteristics and applications of structural laminated veneer lumber made from planted forest wood is introduced, and its preparation is explained, including various tree species and slab qualities, treatments for multiple effects and reinforced composites. The relevant factors in the bonding technology and pressing processes as well as the mechanical properties, research direction and application prospects of structural laminated veneer lumber made from planted forest wood are discussed.